Food comsumption and growth of Podisus nigrispinus (Dallas) on Alabama argillacea (Huebner) under laboratory conditions - dos Santos, Terezinha M.; Silva, Evandro N.; Ramalho, Francisco de Sousa (Pesquisa Agropecuaria Brasileira, 1996)
The food consumption and growth of Podisus nigrispinus (Dallas) nymphs on second, third, fourth, and fifth ínstar larvae of cotton leafworm (Alabania argillacea) were studied in the Biological Control Unit/National Center for Cotton Research/Embrapa, in Campina Grande, PB, Brazil. The results showed that: (1) food consumption and growth of P. nigrispinus is a function of the larvae size of A. argillacea and ínstar of the predator; (2) nymphs of P. nigrispinus show high rate of survival even under condition of food scarcity; (3) nymphs of P. nigrispinus under conditions of food scarcity show lower growth; and (4) the amourit of available food has influence on the physiological and biological state of P. nigrispinus.